Implementation of the Habitual Tahfiz Juz 30 in Improving the Quality of Students' Memorization at MIM Gembuk II - Marfiah Marfiah; Ahmadi Ahmadi (Lembaga Yasin AlSys, 2026)
The need to cultivate learning behaviors that improve the quality of Qur’anic memorization from an early age, particularly in Juz 30, provides the basis for this study. This study aims to describe the implementation of tahfiz habituation and explore its influence on the memorization ability of students at MIM Gembuk II. A descriptive qualitative approach was employed, with data collected through observation, interviews, and documentation. The findings indicate that tahfiz habituation was implemented through routine practices, particularly muroja’ah and teacher-guided memorization sessions. The program was supported by teachers’ active involvement, a positive school environment, and family participation. Its influence was reflected in students’ improved memorization quality, particularly in terms of accuracy, fluency, and memorization mastery. The study concludes that regularly guided tahfiz habituation can serve as an effective Qur’anic learning strategy at the Madrasah Ibtidaiyah level. These findings contribute to the development of structured memorization practices in Islamic elementary education and highlight the importance of sustained school–family collaboration in strengthening students’ Qur’anic memorization quality.